SISTEM PEMANTAUAN KUALITAS UDARA SECARA REAL-TIME MENGGUNAKAN ESP32 DAN TEKNOLOGI IOT - Rahmi Hidayati (Universitas Dharmawangsa, 2024)
Air quality is the level of cleanliness or air pollution in a certain area. Poor air quality hurts human health and the environment. One of the negative impacts of air quality is caused by forest burning, which causes haze. To overcome this problem, we can use Internet of Things (IoT) technology by building an air quality monitoring system. This research aims to provide air quality information to users by accessing a website that will display real-time data. This system can be utilized by the community to find out the air quality around their residence. The research method uses a waterfall model, which includes requirements analysis, system design, implementation, and testing. The data used is air quality data in Pontianak City, including temperature, humidity, CO, CO2, O2 and dust. The test results for 18 days showed normal values for temperature, humidity, and CO2, while the dust and CO2 sensors showed an increase in value with different category levels, with the lowest value of the dust sensor being 21 µg/m3 and the highest value being 497 µg/m3, while the CO2 value ranged from 433 ppm to 5441 ppm.